Effect of Vitamin C, Hydrocortisone, and Thiamine vs Hydrocortisone Alone on Time Alive and Free of Vasopressor Support among Patients with Septic Shock: The VITAMINS Randomized Clinical Trial - Tomoko Fujii (2020)
© 2020 American Medical Association. All rights reserved. Importance: It is unclear whether vitamin C, hydrocortisone, and thiamine are more effective than hydrocortisone alone in expediting resolution of septic shock. Objective: To determine whether the combination of vitamin C, hydrocortisone, and thiamine, compared with hydrocortisone alone, improves the duration of time alive and free of vasopressor administration in patients with septic shock. Design, Setting, and Participants: Multicenter, open-label, randomized clinical trial conducted in 10 intensive care units in Australia, New Zealand, and Brazil that recruited 216 patients fulfilling the Sepsis-3 definition of septic shock. The first patient was enrolled on May 8, 2018, and the last on July 9, 2019. The final date of follow-up was October 6, 2019. Interventions: Patients were randomized to the intervention group (n = 109), consisting of intravenous vitamin C (1.5 g every 6 hours), hydrocortisone (50 mg every 6 hours), and thiamine (200 mg every 12 hours), or to the control group (n = 107), consisting of intravenous hydrocortisone (50 mg every 6 hours) alone until shock resolution or up to 10 days. Main Outcomes and Measures: The primary trial outcome was duration of time alive and free of vasopressor administration up to day 7. Ten secondary outcomes were prespecified, including 90-day mortality. Results: Among 216 patients who were randomized, 211 provided consent and completed the primary outcome measurement (mean age, 61.7 years [SD, 15.0]; 133 men [63%]). Time alive and vasopressor free up to day 7 was 122.1 hours (interquartile range [IQR], 76.3-145.4 hours) in the intervention group and 124.6 hours (IQR, 82.1-147.0 hours) in the control group; the median of all paired differences was-0.6 hours (95% CI,-8.3 to 7.2 hours; P =.83). Of 10 prespecified secondary outcomes, 9 showed no statistically significant difference. Ninety-day mortality was 30/105 (28.6%) in the intervention group and 25/102 (24.5%) in the control group (hazard ratio, 1.18; 95% CI, 0.69-2.00). No serious adverse events were reported. Conclusions and Relevance: In patients with septic shock, treatment with intravenous vitamin C, hydrocortisone, and thiamine, compared with intravenous hydrocortisone alone, did not significantly improve the duration of time alive and free of vasopressor administration over 7 days. The finding suggests that treatment with intravenous vitamin C, hydrocortisone, and thiamine does not lead to a more rapid resolution of septic shock compared with intravenous hydrocortisone alone.